The Bondelswarts Rebellion of 1922 - Lewis, Gavin, 1954- (Rhodes University, Faculty of Humanities, Department of History, 1978)
The rebellion was the result of many and varied Bondelswarts grievances, accumulating into discontent. The attempted arrest of Morris and the bungling of subsequent negotiations was the last straw. Their distrust, fear and suspicion of the Government, built up from German times, made any negotiations doubly difficult. They were a proud people, proud of their history and traditions, and proud of their tribal identity. Their days of complete independence were not long gone, and only in the early 1920's was there any appreciable white settlement in their area. It was then, while they watched their lands being irrevocably divided up amongst whites, that with the increased white settlement came stricter and more burdensome laws. In some respect, the rebellion was the last stand of a people driven to frustration and poverty. It was indeed, as Freislich calls it, the last tribal war. They fought a futile battle against the inexorable advance of white technology and civilization, and in this sense their ultimate revolt was perhaps inevitable (Conclusion: p. 229-230)
Keywords: Bondelswarts (African people); Namibia -- Race relations; Namibia -- History